HOTS study primary teacher education UNNES students based on self-regulated learning - Nursiwi Nugraheni; St. Budi Waluya; Walid Walid (Jurnal Prima Edukasia, 2021)
This research aims to study students’ High Order Thinking Skills (HOTS) in the Primary Teacher Education Department of Universitas Negeri Semarang (UNNES) viewed from their Self-Regulated Learning (SRL). The research method in this research is a mixed method of a sequential explanatory model. This research was conducted in the Department of Primary Teacher Education at UNNES for students of class 2020 in the Basic Mathematical Concept course. Data collection techniques using questionnaires, documentation, interviews. Analysis of quantitative data in the form of validity and reliability of the instrument was followed by descriptive analysis. Qualitative data analysis was performed by triangulation and descriptive statistical analysis. Analysis of quantitative data found two categories of the level of SRL, namely medium and high levels. The results of the analysis of student answers were obtained: (1) Students with moderate SRL category interpret the questions into Mathematical language, and the way they identified the problem is less communicative, while the students with high SRL category interpret the questions into Mathematical language communicatively; (2) Based on students’ ability to evaluate, students with moderate SRL category have not been fluent yet, while the students with high SRL category have been fluent in evaluating, and (3) Based on their creativity, students with moderate SRL still need more practices, while students with high SRL category have been fluent. The conclusion of this study is the ability to interpret problems and the habit of examining problem-solving carried out into the differences between the two categories.